2016
DOI: 10.14687/ijhs.v13i1.3498
|View full text |Cite
|
Sign up to set email alerts
|

To what extent do Turkish high school students know about their body organs and organ systems?

Abstract: This study aimed to determine high school students' familiarity with body organs and knowledge about the systems to which organs belong. It also identifies their misconceptions and deficiencies and discusses their causes. The sample of the study consisted of 244 secondary students. The study used the descriptive survey method. The findings show that the heart, lungs, kidneys and stomach are the best known organs by the students, and that they most often identified organs in the circulatory, respiratory, urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…Then, the most frequently drawn organs were the liver, oesophagus, kidneys and intestines, respectively. This finding is consistent with the study conducted by Aydın (2016), and Stears and Dempster (2017).…”
Section: Resultssupporting
confidence: 93%
“…Then, the most frequently drawn organs were the liver, oesophagus, kidneys and intestines, respectively. This finding is consistent with the study conducted by Aydın (2016), and Stears and Dempster (2017).…”
Section: Resultssupporting
confidence: 93%
“…(Prokop, 2006) menyebutkan bahwa beberapa siswa memiliki pemahaman yang buruk tentang organ-organ yang berfungsi sebagai tempat berlangsungnya proses pencernaan makanan. Selanjutnya, Aydin (2016) berpendapat bahwa masih banyak siswa yang mengalami kesulitan menjelaskan fungsi organ-organ pada sistem pencernaan. Sistem pencernaan manusia merupakan materi yang membahas mekanisme pencernaan manusia dalam memproses zat makanan yang masuk ke dalam tubuh melalui saluran pencernaan.…”
Section: Pendahuluanunclassified
“…Several studies in literature have already identified some misconceptions in science through all ages and gender in education (Aydın, 2016;Özgür, 2013;Sami, 2013). Students' naïve beliefs (Caramazza, McCloskey, & Green, 1980); or alternative conceptions (Arnaudin & Mintzes, 1985); children science (Gilbert, Osborne, & Fenshman, 1982) different than the scientific phenomenon is called as misconceptions (Fisher, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…If students' misconceptions can be elicited then the meaningful learning can be achieved (Hipkins et al, 2002). Aydın (2016) found that one of the common misconceptions held in biology is to list liver as an excretory organ. Best known organs by the students were reported as heart, lungs, kidneys, and stomach and they are identified in circulatory system, respiratory system, urinary system, and digestive system correctly by the students (Aydın, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation